Studi Komparatif Motivasi dan Prestasi Belajar Taruna AAL Ditinjau dari Pilihan Korps Untuk Mewujudkan World Class Navy - Koko Komarudin (Biokultur, 2020)
The interest of cadets is one of the considerations to determine their Service Corps while studying in the Naval Academy; though, it bears the least point compared among other aspects.  Based on some views of educational experts, interest is a motivational tool that can arouse the excitement of learning. Hypothetically, cadets who have good motivation to learn are feasibly able to get better achievement. The author carried out the study to find out the distinction of motivation and learning achievement between cadets with the corps of their interests and those whose corps are not on their interests: the influencing factors upon motivation and learning achievement; and simulation of dynamic system of motivation and achievement with the samples of 4th-grader  Cadets of 62 in Indonesian Naval Academy.  By using the results of independent t-test with a value greater than 0.05.  apparently there is no significant differences of motivation and learning achievement  among the cadets with different corps in relevance  with their interests. Then based on the descriptive analysis, factors that influence the motivation and learning achievement are: the instructors and the cadres, teaching materials, teaching and learning facilities and learning social environment with the  average  point of 84.25% of satisfaction level. The result from the dynamic system simulation model tells that the respondents who have very good level of interest and are supported optimally by  the influencing  factors, are able to achieve GPA 3.6. It proves that interest, motivation and influencing factors come in linear to better achievement among cadets. Therefore, it is necessary to conduct regular and organized  evaluation toward learning factors for optimal learning achievement of cadets.